2016
DOI: 10.1103/physrevlett.116.147804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrodynamics from Memory Kernels

Abstract: The memory kernel for a tagged particle in a fluid, computed from molecular dynamics simulations, decays algebraically as t −3/2 . We show how the hydrodynamic Basset-Boussinesq force naturally emerges from this long-time tail and generalize the concept of hydrodynamic added mass. This mass term is negative in the present case of a molecular solute, at odds with incompressible hydrodynamics predictions. We finally discuss the various contributions to the friction, the associated time scales and the cross-over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 32 publications
1
84
0
Order By: Relevance
“…This was due to accumulating errors when applying the inverse Volterra technique, which became most pronounced at large correlation times. In our applications here, we found the IMRV method to be more robust than other non-iterative memory reconstruction techniques [34][35][36][37][38][39] . Fig.…”
Section: Reconstruction Of Distance-dependent Memory Kernelsmentioning
confidence: 73%
“…This was due to accumulating errors when applying the inverse Volterra technique, which became most pronounced at large correlation times. In our applications here, we found the IMRV method to be more robust than other non-iterative memory reconstruction techniques [34][35][36][37][38][39] . Fig.…”
Section: Reconstruction Of Distance-dependent Memory Kernelsmentioning
confidence: 73%
“…120,121 From the ratio of the added mass and the particle mass M2m=ρ2ρB, it is simple to see that for a lighter fluid the compressibility becomes less important for the particle dynamics.…”
Section: Hydrodynamic Modelmentioning
confidence: 99%
“…Such slow hydrodynamic modes also manifest themselves in the non-Markovian dynamics of solutes, which includes a deterministic component of the force exerted by the suspending fluid, well described for colloidal spheres by the Basset-Boussinesq force [20,21]. Simulations displaying such a hydrodynamic memory, either on a coarse-grained [22] or molecular [23] scale, may therefore suffer from artefacts associated with the use of PBC, at least on long time scales. This was already recognized by Alder and Wainwright in their seminal paper where they reported their results "up to the time where serious interference between neighbouring periodically repeated systems is indicated" [24].…”
mentioning
confidence: 99%
“…Similarly, it has been recently shown that the diffusion coefficient of lipids and carbon nanotubes embedded in a membrane diverges logarithmically with system size [11] and one should also observe the impact of PBC on the transient dynamics. This may also prove important for extracting from finite size simulations other dynamical properties for which hydrodynamics play an important role, such as memory kernels [23].…”
mentioning
confidence: 99%